Wireless power and intelligent harvesting for internet of things (IoT) - Thet, Zaw Htet (Nanyang Technological University, 2019)
This paper presents the study of efficient wireless power transfer (WPT) system by designing, simulation and fabrication of symmetric strongly coupled printed resonators for wireless charging applications. Firstly, the literature review on many research papers are carried out to understand the working principles of wireless power transfer in various designs. Then, designing 3D model of different design structures in CST microwave studio software environment is performed followed by simulation and analysis of the results. At last, the successfully optimized wireless power transfer 3D model designs are sent out for fabrication to perform hardware testing. In this research project, symmetric strongly coupled printed resonators (SCPR) are used in representing three different prototypes of simple compact design for wireless charging applications. The project model is comprised of two substrates, the transmitting substrate in which a driving loop on the top layer and the high Q-resonator on the bottom layer are constructed, as well as receiving substrate in which the high Q-resonator is constructed as the receiver and the load as the loop. The primary focus of the project is to achieve a high wireless power transfer (WPT) efficiency at the operating frequency of 100 MHz. The proposed designs manage to achieve good WPT efficiencies through circuit simulations, electromagnetic simulations and measurements.